2022
DOI: 10.3389/fbioe.2022.941623
|View full text |Cite
|
Sign up to set email alerts
|

3D in vitro Models of Pathological Skeletal Muscle: Which Cells and Scaffolds to Elect?

Abstract: Skeletal muscle is a fundamental tissue of the human body with great plasticity and adaptation to diseases and injuries. Recreating this tissue in vitro helps not only to deepen its functionality, but also to simulate pathophysiological processes. In this review we discuss the generation of human skeletal muscle three-dimensional (3D) models obtained through tissue engineering approaches. First, we present an overview of the most severe myopathies and the two key players involved: the variety of cells composin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 155 publications
(184 reference statements)
0
11
0
Order By: Relevance
“…However, microscopic observations of muscle tissue have shown that this classification may be relatively arbitrary and that the endomysium and perimysium form two continuous 3D networks [211,213]. Furthermore, according to some classification schemes, the basal lamina is considered to be a distinct structure from the endomysium; however, they are in close contact, and in some instances, the basal lamina has been described as a specialized form of endomysium [214,215]. Generally, the major component of muscle ECM is collagen, accounting for up to 10% of its dry weight [200,211].…”
Section: Modeling Aging-related Muscle Degenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…However, microscopic observations of muscle tissue have shown that this classification may be relatively arbitrary and that the endomysium and perimysium form two continuous 3D networks [211,213]. Furthermore, according to some classification schemes, the basal lamina is considered to be a distinct structure from the endomysium; however, they are in close contact, and in some instances, the basal lamina has been described as a specialized form of endomysium [214,215]. Generally, the major component of muscle ECM is collagen, accounting for up to 10% of its dry weight [200,211].…”
Section: Modeling Aging-related Muscle Degenerationmentioning
confidence: 99%
“…The epimysium is formed of collagen type I, collagen type III, and fibronectin; the perimysium contains fibronectin, proteoglycans, and collagens I, III, V, and VI; and the endomysium is composed of laminin, fibronectin, and collagens I, III, and V [218][219][220][221]. Collagen IV, the collagenous component of basement membranes, has also been isolated from the endomysium, where it links with laminin to form a complex involved in force transduction [214,218]. Some studies suggest that collagen type I is the main component of intramuscular ECM and that it is abundant in the perimysium and epimysium, while collagen type III is evenly distributed between the endomysium and the epimysium [214,218,222].…”
Section: Modeling Aging-related Muscle Degenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…In VML injuries, the MuSC pool is depleted through the loss of muscle volume, infringing on muscle’s inherent regenerative capacity [ 1 , 2 ]. In addition, extracellular matrix (ECM) accounts for ~10% of the skeletal muscle mass and coats muscle fibers and MuSCs [ 3 ]. Loss of the ECM eliminates a key element in muscle regeneration.…”
Section: Introductionmentioning
confidence: 99%